Tremella fuciformis Polysaccharides Attenuate Oxidative Stress and Inflammation in Macrophages through miR-155 - Yang Ruan; Hong Li; Lianmei Pu; Tao Shen; Zening Jin (Analytical Cellular Pathology)
Aim. To investigate the function of Tremella fuciformis polysaccharides (TFPS) in LPS-induced inflammation and oxidative stress of macrophages. Methods. RAW264.7 cells were pretreated with TFPS and then stimulated with 0.1 μg/ml LPS. NFκB, Akt, p38MAPK, MCP-1, and SOD-1 were analyzed by Western blotting. Cell viability was measured using MTT assays. Reactive oxygen species (ROS) production, real-time PCR, ELISA, and immunofluorescence staining were performed on RAW264.7 cells that were treated with LPS and/or TFPS to investigate the anti-inflammatory effect of TFPS. Results. LPS induced inflammation and ROS production and promoted the secretion of cytokines such as TNF-α and IL-6. LPS also enhanced the nuclear translocation of NFκB, which promoted inflammation by oxidative stress. However, pretreatment with TFPS profoundly inhibited the activation of Akt, p38MAPK, and NFκB and attenuated the expression of MCP-1 in macrophages. Meanwhile, TFPS also decreased cytokine and ROS levels and attenuated cell inflammation after treatment with LPS. Moreover, miR-155, one of the key small RNAs which regulate NFκB and inflammation in macrophages, was significantly downregulated. Conclusion. TFPS inhibits LPS-induced oxidative stress and inflammation by inhibiting miR-155 expression and NFκB activation in macrophages, which suggests that TFPS may be a potential reagent for inhibiting the development of inflammation.